STRUCTURAL INTERCONNECTIONS OF THE SUBJECTS OF CIRCULATION - Tkachenko, Serhii (Social Economics, 2020)
The aim of the article is justification of the classification of subjects in a sphere of circulation of goods, which is due to their significant diversity, which is associated with the content of the process of promoting the final product from the supplier to the consumer through a system of warehouses, information support of the market, financing producers, providing services that accompany the movement of goods, future maintenance, state participation in the regulation of the commodity market. The article substantiates the system of activity of the economic entities of the sphere of circulation as an interconnected complex, which contains the structures providing intermediary activities aimed at interaction through the creation of market institutions. A classification of wholesalers has been developed, which includes brokers, consignees, and business entities that carry out catalog sales. The specificity of their activity is determined. It is proved that transport security of commodity markets is one of the most important conditions for positive dynamics of economic growth and dynamic development of the economy of the sphere of circulation, and in the content of its activity the warehouse economy is closely connected with the activity of transport organizations, which are an independent subject of circulation of goods. It is proved that the most important elements of state regulation in the sphere of circulation include strategic forecasting and planning of socio-economic development, including the development of the consumer market, promotion of competition, support of small business, a set of measures to regulate pricing policy, taxation of economic entities and more. The functions of the subjects of circulation have been improved due to the development of the commodity market and the expansion of the scope of management and marketing tools in the activity of economic entities, including logistic tools. It is suggested that the basic functions of the subjects of the turnover should be divided according to the subject of influence (consumers, manufacturers, society in general) and the tools used (logistic and marketing).